Molecular cloning and characterization of the Candida albicans enolase gene. - Mason, A B (1993)
A DNA clone containing the putative Candida albicans enolase gene (ENO1) was isolated from a genomic DNA library. The sequenced insert contained a continuous open reading frame of 1,320 bp. The predicted 440-amino-acid protein is 78 and 76% identical, respectively, to Saccharomyces cerevisiae enolase proteins 1 and 2. Only one enolase gene could be detected in C. albicans genomic DNA by Southern analysis with a homologous probe. Northern (RNA) analysis detected a single, abundant C. albicans ENO1 transcript of approximately 1,600 nucleotides. When cells were grown on glucose, levels of ENO1 mRNA were markedly increased by comparison with ENO1 mRNA levels in cells grown on ethanol, a gluconeogenic carbon source. In contrast to this glucose-mediated transcriptional induction, the carbon source had no dramatic effect on the levels of enolase protein or enzyme activity in the C. albicans strains tested. These results suggest that posttranscriptional mechanisms are responsible for modulating expression of the C. albicans enolase gene.